Restriction fragment analysis of the ribosomal DNA of Paratelmatobius and Scythrophrys species (Anura, Leptodactylidae) - Lourenço, Luciana B.; Garcia, Paulo C.A. [UNESP]; Recco-Pimentel, Shirlei M. (Sociedade Brasileira de Genética, 2003)
Physical maps of the ribosomal RNA gene 28S of species belonging to the genera Paratelmatobius and Scythrophrys were constructed, using five restriction endonucleases. The restriction sites for Bam HI, Bgl II, Bst EII, and Eco RI had similar positions in all species, although there were interspecific differences in the size of the restriction fragments obtained. An additional Pvu II site was found in Scythrophrys specimens from Piraquara (State of Paraná, Brazil) and from São Bento do Sul (State of Santa Catarina, Brazil), but not in the Scythrophrys specimens from Rancho Queimado (State of Santa Catarina, Brazil). This finding is in agreement with the hypothesis regarding the existence of two species in the genus Scythrophrys. on the other hand, the extra Bst EII site considered in the literature to be a synapomorphy for the subfamilies Leptodactylinae and Telmatobiinae was not observed in the genera Paratelmatobius and Scythrophrys, which brings new questions about some taxonomic classifications that include Paratelmatobius in Leptodactylinae and Scythrophrys in Telmatobiinae. Interspecific variation was observed in the size of the restriction fragments analyzed and, in the case of group I Scythrophrys, there was also a variation between the individuals of the two populations. These data suggest that sequencing of the rDNA segments studied here may be useful in phylogenetic studies of the genera Paratelmatobius and Scythrophrys.
Keywords: ribosomal DNA; 28S rDNA gene; restriction sites; physical map; Paratelmatobius; Scythrophrys; Leptodactylidae; Anura